The Role of Market Orientation, Marketing Capability and Promotion on The Marketing Performance of MSME Flower Shops in Yogyakarta - Sera Nopita Asri; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how market orientation, marketing capability, and promotion affect Yogyakarta's flower shop MSMEs' marketing performance. In this study, 45 responders made up the sample. A questionnaire is utilized as the study instrument in this non-probability sampling strategy. The study's findings demonstrate that: (1) Market orientation has no discernible impact on marketing performance. (2) Marketing Performance is positively and significantly impacted by Marketing Capability. (3) The Marketing Performance is not much impacted by promotion. (4) The marketing performance of Yogyakarta's flower shop MSMEs is significantly impacted by market orientation, marketing capability, and stimulant promotion.